Diagnostic challenges of central nervous system infection: extensive multiplex panels versus stepwise guided approach. (June 2020) - Vetter, P.; Schibler, M.; Herrmann, J.L.; Boutolleau, D.
Abstract: Background: Cerebrospinal fluid (CSF) testing is a key component for the diagnosis of central nervous system (CNS) infections. Current meningitis and encephalitis management guidelines agree on the need for CSF molecular testing in combination with other direct and indirect biological testing, both in CSF and blood. Multiplex molecular tests have been developed to reduce turnaround times and facilitate the diagnostic approach. Objectives: We aim to discuss the role of multiplex molecular panels in the management of CNS infections. Sources: The MEDLINE database and the grey literature have been searched for relevant articles. Content: New molecular multiplex panels are being developed to simultaneously detect a large array of neuropathogens in CSF. Although one of these assays has been US Food and Drug Administration-approved, extensive analytical and clinical validation is still missing, and suboptimal performance related issues have been raised. Its use has been associated with decreased costs, reduced length of hospital stay and reduced antiviral therapy administration in retrospective, industry-sponsored studies. The pros and cons of this multiplex syndromic approach are discussed in this narrative review. Implications: Molecular multiplex CNS infection diagnosis panels have been developed and present several attractive features, including ease of use and low turnaround time. However, suboptimal analytical performances render these tests difficult to use without additional confirmatory tests. Such panels are not comprehensive nor adapted to all situations, depending on the epidemiological or clinical context. Overall, available data in the literature currently do not support the use of a multiplex PCR panel in clinical routine as a 'stand-alone' molecular assay. Except in restricted laboratory capacity settings where such easy-to-use multiplex panels offer the diagnostic means that would otherwise not be available, the stepwise testing approach remains a more rational option. Serological testing both in blood and CSF should not be neglected, but it represents essential complementary tools regarding some neuropathogens.